An ANALYSIS OF DVB-T2 TV BROADCAST TESTING DRIVE TEST AND FIELD STRENGTH METHODS IN THE JAKARTA SERVICE AREA - Zebua, Nifesrianto; Murti, Budi Bayu (KURVATEK, 2024)
Indonesia has adopted DVB-T2 as the technology standard for terrestrial digital television broadcasting. This research aims to test and analyze the reception quality of DVB-T2 TV broadcasts in the DKI Jakarta service area. The research was conducted using drive test and field strength methods to test and evaluate the quality of digital television broadcasts. Tests were conducted in various locations in the DKI Jakarta service area using the Gsertel Hexylon TV Analyzer technical device to test DVB-T2 TV broadcast signals. The field strength test results were more accurate and higher values were generated than the drive test. Several parameters such as signal level and MER are evaluated and analyzed to find out what affects their values. The transmitter parameter settings such as modulation, FEC code rate, FFT Mode, Guard Interval, and Pilot Pattern greatly affect the signal level and MER values. The optimization performed on CH 24 also managed to maintain its signal level value of 18.19 dB and its MER of 55.01 dBÂµV to maintain broadcast stability during a technical failure of the transmitter on CH 1.